INCLUSIVE EDUCATION IN BIOLOGY TEACHING (Лучшие интеллектуальные исследования, 2025)
Abstract: The article provides information about the requirements for a modern teacher, the technologies needed to improve the effectiveness and application of the lesson, information aimed at ensuring the effective use of modern technologies by a modern teacher, information about inclusive education